Successful Traceability of Wildlife Samples Contributes to Wildlife Conservation: A Case Study of Tracing the Snub-Nosed Monkey (Rhinopithecus spp.) - Xibo Wang; Ying Shen; Yang Teng; Ruifeng Wu; Shuhao Liu; Jilai Zhao; Can Hu; Ming Li; Huijuan Pan; Jiwei Qi (Animals)
Rapid and effective methods for tracing the geographic origin of wildlife samples are essential for tackling the illegal wildlife trade. Traditional morphological categorization methods are often inadequate as relying on the mitochondrial COXI barcode is insufficient for determining geographic populations. To address these limitations, we developed a bioinformatics-based pipeline for the rapid identification of traceable nuclear genome loci. This pipeline has been applied to the whole-genome sequence (WGS) data of China’s flagship species, the snub-nosed monkey (Rhinopithecus spp.). These species are known for sex-biased dispersal and hybrid speciation, which complicates genealogy tracing. Using phylogenetic principles, we employed the Robinson and Foulds (RF) distance and scanned over 1,850,726 population-specific loci, identifying five pairs that can trace genealogy origins rapidly and cost-effectively using PCR. Additionally, we found that relying only on mitochondrial genetic information is insufficient for rapid and accurate traceability to subspecies-level geographic populations. Our pipeline efficiently identifies loci and traces the geographic origin of snub-nosed monkey individuals, providing a valuable tool for species preservation and combating the wildlife trade. This approach can be extended to other species, aiding in the conservation of endangered wildlife and tracing criminal evidence.